1993
DOI: 10.1021/jm00060a014
|View full text |Cite
|
Sign up to set email alerts
|

Centrally acting serotonergic and dopaminergic agents. 1. Synthesis and structure-activity relationships of 2,3,3a,4,5,9b-hexahydro-1H-benz[e]indole derivatives

Abstract: The synthesis and structure-activity relationships (SAR) of 2,3,3a,4,5,9b-hexahydro-1H-benz[e]indole derivatives (3) are described. These compounds are conformationally restricted, angular tricyclic analogs of 2-aminotetralin. The synthesis was achieved in several steps from the corresponding 2-tetralones. The enantiomers of the cis analogs were obtained from either fractional recrystallizations of the diastereomeric salts of di-p-toluoyl-L-(or D)-tartaric acid or an asymmetric synthesis using chiral (R)-alpha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

1993
1993
2015
2015

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 20 publications
0
9
0
Order By: Relevance
“…In an earlier report on the structure-activity relationships (SAR) of 2,3,3a,4,5,9b-hexahydro-l/i-benz[e] indole 2 3 derivatives (1), we demonstrated that the more rigid five/ six fused angular tricyclic 2-aminotetralins indeed show interesting pharmacological properties. 1 In this series, we found that the cis analogs are more potent than the corresponding trans analogs. Analogs with 9-methoxy substitution (Ri) showed mixed 5-HTia receptor agonist that all cis analogs were completely inactive.…”
Section: Introductionmentioning
confidence: 82%
See 1 more Smart Citation
“…In an earlier report on the structure-activity relationships (SAR) of 2,3,3a,4,5,9b-hexahydro-l/i-benz[e] indole 2 3 derivatives (1), we demonstrated that the more rigid five/ six fused angular tricyclic 2-aminotetralins indeed show interesting pharmacological properties. 1 In this series, we found that the cis analogs are more potent than the corresponding trans analogs. Analogs with 9-methoxy substitution (Ri) showed mixed 5-HTia receptor agonist that all cis analogs were completely inactive.…”
Section: Introductionmentioning
confidence: 82%
“…Since our previous SAR study on angular tricyclic analogs (1) showed that a more rigid five/six fused ring structure could indeed improve their pharmacological profile, we thought it would be interesting to examine similar analogs in the linear tricyclic series. Analogs represented by the generic structure 3, 2,3,3a,4,9,9ahexahydro-lH-benz [/] indole derivatives, would be more conformationally restricted than six/six fused ring analogs 2.…”
Section: Introductionmentioning
confidence: 99%
“…The absolute configuration of allylated tetralone 11 was established by the synthesis of the known pyrrolidine‐fused tetralin 13 , a family of molecules that has attracted attention due to their serotonin and dopamine agonist activity 11. 12 To this end, the terminal olefin of tetralone 11 was oxidatively cleaved to give unstable keto aldehyde 12 . Aldehyde 12 was reductively aminated with benzhydrylamine and then the tertiary amine was deprotected by hydrogenation with Pearlman's catalyst to give aminotetralin 13 .…”
Section: Selected Optimization Studies Of the Aaa Of 2‐phenylcyclohexmentioning
confidence: 99%
“…In an earlier report, we described the SAR on rigid five-/six-fuxed angular tricyclic 2-aminotetralins, 2,3,3a,4,5,-9b-hexahydro-l.£f-benz[e]indole derivatives (2). 8 The analogs, where Rj = OH or OMe and R2 = propyl or allyl, were found to display potent 5-HTia receptor agonist activity. Our study showed that the cis analogs are more potent than the corresponding trans analogs with 5-HTia activity residing in the m-(3aff)-enantiomer.…”
Section: Introductionmentioning
confidence: 99%
“…Fortunately, the 1:1 maleate salt of (-)-3a, U93385E, produced a crystalline form possessing excellent physicochemical properties suitable for drug formulation (see the Experimental Section). 16 In the second synthesis, as outlined in Scheme II, 8-bromo-2-tetralone (8) was used as the starting material. 16 Regioselective alkylation of the C-l position of tetralone 8 with methyl bromoacetate was carried out by using LDA as the base, yielding the keto ester 9 in 80-85% yield.8 Reductive amination/cyclization of this keto ester 9 with (R)-a-methylbenzylamine afforded the mixture of diastereomeric lactams 10a/10b.17 The mixture of diastereomers was separated by chromatography using the Waters prep-500 HPLC.…”
Section: Introductionmentioning
confidence: 99%